Application of International Standards to Evaluate the Potential of Sustainable Secondary Production of Tin and Tungsten in Portugal - Md Ariful Islam; José E. Brito Iria; Georg Meissner; George Barakos; Helmut Mischo (Materials Proceedings, 2023)
The ambitious movement towards industry 5.0 technologies and the green transition drives the efforts towards securing critical metals’ supply chains globally. In Europe, highly economically important Tin and Tungsten are raising concerns regarding supply security due to geographical reserves’ uniformity and socio-political reluctance to mining. Nevertheless, mines that have seized operations in Portugal due to not being sustainable in the past are attracting renewed attention for further exploitation due to growing market demand and reclamation efforts for environmental concerns. Such abandoned resources need to be reassessed for their feasibility from economic, social, and environmental perspectives to ensure sustainable exploitation. Presenting the production criticality of Tin and Tungsten, this study implements the United Nations Framework Classification for Resources (UNFC) to assess the viability of abandoned mines and tailings dumps in Portugal, considering the indicators of Sustainable Development Goals (SDGs). The work indicates that Portugal’s abandoned Vale das Gatas Tin and Tungsten mine has good potential for further development. Furthermore, social perception towards new and abandoned mining is evaluated by collecting opinions from different parts of the country. It has been identified that sustainable technology and job opportunities are the driving parameters for the social acceptance of mining projects in Portugal.